Identification of Pediatric Oral Health Core Competencies through Interprofessional Education and Practice - D. Hallas; J. B. Fernandez; N. G. Herman; A. Moursi (Nursing Research and Practice)
Over the past seven years, the Department of Pediatric Dentistry at New York University College of Dentistry (NYUCD) and the Advanced Practice: Pediatrics and the Pediatric Nurse Practitioner (PNP) program at New York University College of Nursing (NYUCN) have engaged in a program of formal educational activities with the specific goals of advancing interprofessional education, evidence-based practice, and interprofessional strategies to improve the oral-systemic health of infants and young children. Mentoring interprofessional students in all health care professions to collaboratively assess, analyze, and care-manage patients demands that faculty reflect on current practices and determine ways to enhance the curriculum to include evidence-based scholarly activities, opportunities for interprofessional education and practice, and interprofessional socialization. Through the processes of interprofessional education and practice, the pediatric nursing and dental faculty identified interprofessional performance and affective oral health core competencies for all dental and pediatric primary care providers. Students demonstrated achievement of interprofessional core competencies, after completing the interprofessional educational clinical practice activities at Head Start programs that included interprofessional evidence-based collaborative practice, case analyses, and presentations with scholarly discussions that explored ways to improve the oral health of diverse pediatric populations. The goal of improving the oral health of all children begins with interprofessional education that lays the foundations for interprofessional practice.